Innovative clusters – regional level and global effect (Journal of Economic Research & Business Administration, 2015)
The article is devoted to the concept of innovative clusters and their features. Here the reasons of favorable business ecosystem, appearing within innovative clusters, are analyzed. Such business ecosystem provides prerequisites for higher effectiveness of cluster companies and their competitive advantage as well as of region and country as a whole. The main factors, conditioning creation of innovative clusters or transformation of industrial clusters into innovative, are considered. Economic effects of innovative clusters on firms, regions, countries and global level are analyzed and described. The reasons of Kazakhstan’s state cluster policy failure are presented. Their overcoming will allow launching a process of transformation of existing industrial agglomerations into innovative clusters.
Keywords: innovative cluster; competitive advantage; innovations; globalization; economic development